Building From the Bottom Up: The Importance of Tier 1 Supports in the Context of Tier 2 Interventions. (January 2021) - Van Camp, Alyssa M.; Wehby, Joseph H.; Copeland, Bailey A.; Bruhn, Allison L.
School-Wide Positive Behavior Interventions and Supports (SWPBIS) relies on effective implementation of Tier 1 practices to ensure accurate identification of students in need of more intensive supports at Tier 2 or Tier 3. While measures of school-level fidelity are widely used, measures of classroom-level implementation of Tier 1 supports are less common. If classroom levels of Tier 1 supports are variable, schools may identify students for Tier 2 supports when, instead, teachers need support implementing Tier 1 in classrooms. The purpose of this case study was to assess the impact of a self-monitoring intervention, Monitoring Behavior on the Go (MoBeGo), on the academic engagement and disruptive behavior of a middle school student. Initially, the impact of the self-monitoring intervention was inadequate. In the context of evaluating the impact of a Tier 2 intervention, we identified an opportunity to assess whether a class-wide Tier 1 program, Class-Wide Function-Related Intervention Teams (CW-FIT), enhanced the effectiveness of the Tier 2 intervention. Using an A-B-BC-B-BC design, we compared the effectiveness of a Tier 2 intervention alone with a combined Tier 1 + Tier 2 intervention. When the class-wide Tier 1 program was layered on top of the Tier 2 intervention, the student's academic engagement showed an increase in level and stability.